2011
DOI: 10.3141/2216-02
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Delay Incident Occurrence in Urban Metros

Abstract: The reliability of train service is a key objective of metro management and a major part of a successful operation. An occurrence of incidents in the network is likely to cause delays to the train service and disorder in the punctuality and regularity of the metro operation and hence affects the service reliability of the metro system. This result suggests a way to improve train service reliability by reducing the occurrence of incidents in urban metro systems. This paper used statistical techniques to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…However this study had insufficient data points available to disaggregate GoA2, GoA3 and GoA4. Reasons that GoA4 could improve reliability include removal of 'driver unavailable' as a reason for cancelled trains (15,23), and reduced opportunity for incidents caused by human error (23,24). Reliability affects both train-km and passenger-km outputs.…”
Section: Efficient Use Of Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…However this study had insufficient data points available to disaggregate GoA2, GoA3 and GoA4. Reasons that GoA4 could improve reliability include removal of 'driver unavailable' as a reason for cancelled trains (15,23), and reduced opportunity for incidents caused by human error (23,24). Reliability affects both train-km and passenger-km outputs.…”
Section: Efficient Use Of Infrastructurementioning
confidence: 99%
“…For example, GoA2 and above can enable higher operational speeds and train frequencies due to Automatic Train Operation (ATO) (21,23). Paris Métro has reported that after upgrading from GoA1 to GoA4, Line 1 requires fewer rolling stock units to provide the same level of service (21).…”
Section: Efficient Use Of Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Capacity is increased by higher operational speeds and train frequencies provided by DTO systems, where the headway can be reduced to 75 s, even to 60 s [19,20]. In addition, DTO systems can reduce the turnaround times at the terminus to enable higher frequency.…”
Section: Increased Capacity and Reliabilitymentioning
confidence: 99%
“…Other research (Melo et al, 2011) has shown that increasing available line capacity (e.g. with new signalling) reduces delays whereas increasing uptake of that capacity by trains increases delays.…”
Section: Rolling Stockmentioning
confidence: 99%